Encouraging learners to seek and explain communicability issues about Consent Request - Da Silva, Wesley Nunes; Silva, Mônica; Salgado, Luciana C. De Castro (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2023: Anais do XXII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2023)
The General Data Protection Law imposes that obtaining consent is an essential requirement for processing personal data. In the online environment, consent banners use cookies to collect personal data. However, research indicates that these consent requests often do not provide enough information for the user to grant or deny consent. Interaction designers play a crucial role in this context, as they must consider users’ rights while creating interaction technologies. This article presents an experience report on the use of a guide based on the Semiotic Inspection Method to help learners to investigate and reflect about consent terms communicability on websites. We carried out a study with undergraduate students of a Human-Computer Interaction discipline, where each student used the guide to inspect two news portals to identify communication breakdowns and suggest solutions for identified data privacy problems based on an inspection scenario. The results indicate that the guide supported participants identify and explain communicability issues related to non-compliance with the LGPD.